Visual Metaphors in Set and Properties Design for ‘Setengah Nada Bergeming’ Film Trailer - Sethio, Gabriella; Hakim, Salima (VCD, 2022)
In a film production, production design is an important aspect that supports the narrative or story. In production design visual metaphors are often used as concepts for sets and props which have the ability to transform a long text into a shorter visual. Visual metaphor itself is a representation of a place, person, nature, and object that can be a tool to build a narrative as well as describe the nature of a character in a film. The use of visual metaphors can be done by understanding the characters in the film, because each have different characteristics and its own uniqueness. By understanding and using the 3-dimensional aspect of the character as the basis for the design of sets and props, production designers can apply visual metaphors in the design of sets and properties that are suitable for the needs of characters and narratives in films. This paper uses a qualitative approach which elaborates the process of applying visual metaphors into the set and properties design, by using the 3-dimensional character theory as the base for producing the short film trailer entitled Setengah Nada Bergeming. This research finds that by dissecting each element of the 3-dimensional character, production designer can intensify not only how a character is represented and how its contributes in building the entire narrative of the story. Keyword: visual metaphors, 3-D characters, sets, properties, short film, trailer.